Gouvernance territoriale de l’environnement et conflits d’usage. Le cas du bassin versant du lac de Tota (Boyacá, Andes colombiennes) - David Leroy; Alvaro Martín Gutiérrez Malaxechebaría; Jean-Marc Antoine; Alexandra Angéliaume-Descamps (EchoGéo)
The purpose of this work is to show that conflicts play an essential role in the processes of territorial environmental governance. It is based on the case study of the watershed of Lake Tota, the largest lake in Colombia, which is now threatened by the development of several economic activities, and in particular by the intensive cultivation of spring onion. In a context of overexploitation and pollution of the lake's water, environmental conflicts have been exacerbating in recent years between actors the different interests assert themselves a little more each day: rural communities, environmental authorities, environmental associations (Montecito). Revealing the profound changes in this territory, these conflicts will help to take into account environmental problems and allow the various actors to influence decisions. However, the introduction of new forms of coordination between these actors remains an important source of opposition. This is evidenced by the competition between two governance structures (Mesa de trabajo Permanente and Consejo de Cuenca) which highlights the power relations between public authorities and civil society.